2023
DOI: 10.1101/2023.02.21.23286110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative polygenic risk score improves the prediction accuracy of complex traits and diseases

Abstract: Polygenic risk scores (PRS) are an emerging tool to predict the clinical phenotypes and outcomes of individuals. Validation and transferability of existing PRS across independent datasets and diverse ancestries are limited, which hinders the practical utility and exacerbates health disparities. We propose PRSmix, a framework that evaluates and leverages the PRS corpus of a target trait to improve prediction accuracy, and PRSmix+, which incorporates genetically correlated traits to better capture the human gene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…This pattern closely mirrors what is observed in complex human traits [17]. For instance, the prediction accuracy of height, anatomical features being those with best predictions, is around R 2 ∼ 0.2 [30]. This would suggest that genomes are in a regime of low (statistical) prediction (Figure 2).…”
Section: Discussionsupporting
confidence: 79%
“…This pattern closely mirrors what is observed in complex human traits [17]. For instance, the prediction accuracy of height, anatomical features being those with best predictions, is around R 2 ∼ 0.2 [30]. This would suggest that genomes are in a regime of low (statistical) prediction (Figure 2).…”
Section: Discussionsupporting
confidence: 79%
“…Two recent studies, both using simple weighting methods, have shown significant potential for cross-trait borrowing to improve PRS performance for individual traits. 30 , 31 There is, however, likely to be scope for additional improvement by developing formal Bayesian methods that can utilize flexible models for effect-size distribution simultaneously across ancestries and traits.…”
Section: Discussionmentioning
confidence: 99%
“…PRS-CSx, which allows a heavy-tail Strawderman-Berger prior, while theoretically expected to be advantageous for handling such large-effect SNPs, does not show much advantage either. In the future, other heavy-tail type priors such as the Bayesian Lasso (i.e., Laplacian) 32 , Horseshoe 33 , and Bayesian Bridge 34 , are worth investigating. Another potential limitation of the method originates in the SL step: when the tuning sample is small (e.g., <1000), the prediction algorithms utilized in SL may be overfit in the presence of a large number of tuning parameters, ultimately leading to low predictive power in an independent sample.…”
Section: Discussionmentioning
confidence: 99%
“…ME-Bayes SL can also be modified to enhance performance of PRS by borrowing information simultaneously across traits and genetically correlated traits. Two recent studies, both using simple weighting methods, have shown significant potential for cross-trait borrowing to improve PRS performance for individual traits 32,33 . There is, however, likely to be scope for additional improvement by developing formal Bayesian methods that can utilize flexible models for effect-size distribution simultaneously across ancestries and traits.…”
Section: In Our Data Examples Different Methods Show Advantages In Di...mentioning
confidence: 99%